2011
DOI: 10.1016/j.jcin.2010.12.012
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Attenuated Plaque Identified by Intravascular Ultrasound and No-Reflow After Stenting in Acute Myocardial Infarction

Abstract: Attenuated plaque was present in three-quarters of patients with AMI. The amount of attenuated plaque strongly correlated with no-reflow; the larger the attenuated plaque, the greater the likelihood of no-reflow. (Dual Arm Factorial Randomized Trial in Patients w/ST Segment Elevation AMI to Compare the Results of Using Anticoagulation With Either Unfractionated Heparin + Routine GP IIb/IIIa Inhibition or Bivalirudin + Bail-out GP IIb/IIIa Inhibition; and Primary Angioplasty with stent implantation with Either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(53 citation statements)
references
References 37 publications
2
49
0
2
Order By: Relevance
“…[1][2][3][4][5] Histological studies have shown that attenuated plaques contain more necrotic core and fibrofatty tissue or microcalcification compared with fibrous plaques without attenuation. 4,6,7 However, there are limited data on the evolution of attenuated plaques over time.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Histological studies have shown that attenuated plaques contain more necrotic core and fibrofatty tissue or microcalcification compared with fibrous plaques without attenuation. 4,6,7 However, there are limited data on the evolution of attenuated plaques over time.…”
mentioning
confidence: 99%
“…Attenuated plaques are associated with ST-segment elevation MI and no reflow in patients with CAD who undergo PCI (24). However, there has been no systemic review of the impact of attenuated plaques on TIMI grade and clinical outcomes of CAD patients and attenuated plaques are not described in the current IVUS guidelines from the American College of Cardiology or the European Society of Cardiology.…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis by Ding S et al revealed that compared with patients with normal flow, significantly higher absolute necrotic core volume and dense calcium were found in ACS patients with distal embolization (32,33). The HORIZONS-AMI Trial showed that the larger the attenuated plaque is, the greater the likelihood of no-reflow is (24). However, Stone GW et al (7) found that, among 51 non-culprit-lesion related recurrent events occurring in the imaged segments, only 26 (51%) occurred at sites with thincap fibroatheromas while others were the most common thick-cap fibroatheromas.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, attenuated plaques on IVUS correlate with a fibroatheroma containing large necrotic core or pathological intimal thickening (PIT) with a large lipid pool (22). Attenuated plaque is frequently observed at culprit lesion in patients with acute coronary syndrome (ACS) and is associated with deterioration of coronary flow and periprocedural myocardial infarction following PCI (23)(24)(25).…”
Section: Attenuated Plaquementioning
confidence: 99%